A Single 30 Minutes Bout of Combination Physical Exercises Improved Inhibition and Vigor-Mood in Middle-Aged and Older Females: Evidence From a Randomized Controlled Trial - Nouchi, Rui; Nouchi, Haruka; Kawashima, Ryuta (Frontiers in Aging Neuroscience, 2020)
Background Long-term combination of physical exercises has reported benefits for cognitive functions and mood states. However, it remains unclear whether a single bout of combination exercise training has acute positive effects on cognitive functions and mood states in middle-aged and older women. It is important to investigate acute effect of physical exercise because it would help to understand a mechanism of benefits of physical exercise. The purpose of this study was to investigate 30 minutes of a single bout of combination exercise training on cognition and mood states in middle-aged and older females. Methods In this doublesingle-blinded randomized control trial (RCT), middle-aged and older females were assigned randomly to two groups: a combination exercise group and a no-exercise control group. The former group did the combination exercise training (aerobic, strength, and stretching exercises) for 30 minutes. Meanwhile, the latter group did not do any exercise and waited for 30 minutes. We measured cognitive functions and mood performance states before and after the exercise or waiting phasescontrol interventions. Results Our main results demonstrated that, compared to the control group, the combination exercise improved inhibition (reverse Stroop and Stroop) and increased vigor–activity mood scores in both middle-aged and older groups. We also found that the only combination exercise group showed the significant positive correlations between improved inhibition performance and improved vigor-activity mood. Discussion This randomized controlled trial revealed the acute benefits of the combination exercise on inhibition in executive functions and Vigor-Activity in the healthy middle-aged and older females. Our results provided the scientific evidence related to acute effects of the the single bout of the combination exercise training. It suggests that we would be better to do the 30 minutes physical exercise for our health. Trial registration This trial was registered in the University Hospital Medical Information Network Clinical Trials Registry (UMIN000029681). Registered 24 October 2017, https://upload.umin.ac.jp/cgi-bin/ctr/ctr_view_reg.cgi?recptno=R000033922